2006
DOI: 10.1089/end.2006.20.1030
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Percutaneous Tract Dilation on Renal Function and Structure

Abstract: Both animal and human studies show that PCN is associated with an acute decline in renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 24 publications
3
70
0
1
Order By: Relevance
“…In fact, the stimulus to increase PRA may be multifactorial and include tissue injury-related factors (e.g., oxidative stress 16 ) and/or increased renal nerve activity-the sympathetic nervous system having direct and indirect actions on the kidney to increase renin release. 17 We have consistently shown that the EPAH is decreased after PERC procedures 2,9 (present study) and can last at least 3 days postsurgery. 10 PAH is transported from the blood into the renal tubules through selective organic anion transporters (OATs) located on proximal tubule membranes.…”
supporting
confidence: 62%
See 4 more Smart Citations
“…In fact, the stimulus to increase PRA may be multifactorial and include tissue injury-related factors (e.g., oxidative stress 16 ) and/or increased renal nerve activity-the sympathetic nervous system having direct and indirect actions on the kidney to increase renin release. 17 We have consistently shown that the EPAH is decreased after PERC procedures 2,9 (present study) and can last at least 3 days postsurgery. 10 PAH is transported from the blood into the renal tubules through selective organic anion transporters (OATs) located on proximal tubule membranes.…”
supporting
confidence: 62%
“…This is in agreement with our previous animal work, in which we demonstrated that single-tract PERC or multiple-tract PERC to a single kidney results in bilateral renal vasoconstriction. 2,12 Such bilateral renal effects have also been reported in patients undergoing unilateral PCNL. 3,6 The mechanism(s) involved in initiating vasoconstriction in the treated and nontreated kidney and the method of communication between both kidneys are unknown, but could involve the sympathetic nervous system (i.e., reno-renal reflexes) and/or humoral systems.…”
mentioning
confidence: 77%
See 3 more Smart Citations